INOVASI PENGOLAHAN SAMPAH PLASTIK MENJADI PRODUK DAN JASA KREATIF DI KENAGARIAN KINALI KABUPATEN PASAMAN BARAT (Jurnal Hilirisasi IPTEKS, 2021)
Garbage is often regarded as annoying, dirty, and smelly and very difficult to decompose by soil. The most common source of waste is derived from settlements in the form of organic and inorganic waste. Organic waste has been widely used as material for composting, briquettes, and biogas. However, inorganic waste is still very minimal in its management. Inorganic waste that is most often found in the community is plastic waste. Plastic waste is very difficult to be degraded by nature, and if left unchecked, it would be dangerous for the environment. To overcome this, it is necessary to utilize and manage this plastic waste into creative products and services. As an innovative product, plastic trash creations have promising commercial value. This product has a selling power that can generate profits. The purpose of the activity is to provide skills and training in the use of plastic waste into creative products and services for PKK mothers in Kinali, West Pasaman District. The method used is socialization and training. In the training activities, it was given a hands-on practice of making plastic trash artworks accompanied by experienced instructors. This activity also involved lecturers, college students work for Andalas University, and the citizens in Kinali, West Pasaman District. From the results of the event, an increase in art skills for residents of Kinali, West Pasaman District, in processing plastic waste has become more valuable and as an additional income.